ENT 300 Business Plan : Acu Tera Chicken Rice Restaurants / Nur Iman Athirah Mohd Asri … [et al.] - Mohd Asri, Nur Iman Athirah; Nasharudin, Nik Nur Farahani; Mohd Zamri, Nur Zafirah Auni; Nazamira, Nur Aliah Nabihah; Wandi, Noor Fatin Adiba; Muhammad Alias Teaw, Muhammad Fariz (2021)
First and foremost, our business is based partnership. There are six (6) members in this partnership which have important role in the company such as General Manager, Administration Manager, Marketing Manager 1, Marketing Manager 2, Operational Manager and Financial Manager. The business capital is amounted to RM 260,000. Each member total contribution is RM 20,000 and the rest RM 140,000 is from Bank Islam’s loan. Chicken Rice is one of the most popular dish at our company. Acu Tera Chicken Rice Restaurants Sdn Bhd with tagline “Incredible Taste with Diversity Choices” is located near Kota Bharu with address: No 20, Kampung Kraftangan, Jalan Hilir Kota, Bandar Kota Bharu, 15300 Kota Bharu, Kelantan Darul Naim. Acu Tera Chicken Rice Restaurants Sdn Bhd is a company which focuses on food production which selling authentic chicken rice with three different serving portion consists of steamed, roasted or even black pepper chicken in Malaysia. In contrast to regular chicken rice, our company tries to introduce unique food that is interesting and suitable for everyone to enjoy. Apart from that, our company use only the most delicious, freshest and halal ingredients in the making of tasty chicken rice. With this ingredients, our company hope that our chicken rice will attract many people’s attention to try it especially to the people who is chicken rice’s lover. By that, our company highly confident that our business can be easily developed and spread in Malaysia. To make our dish more attractive, our company decided to make some innovation into the chicken as well. For steamed chicken rice, we have put the ginger and minced garlic. Thus, ginger has proven that help aids digestion, reduces nausea and may fight flu and colds while minced garlic can boost the functions of the immune system. Besides that, for black pepper chicken rice, we have added fresh milk and black pepper into this meal. Through this innovation, it helps to increase the body become healthier. By that, our chicken rice may become customers‘s favourite food as it is complete healthy meal which surely satisfying to the tummy. With the loan provide in support of Bank Islam, we hope that Acu Tera Chicken Rice Restaurants can meet the overwhelming demand from consumer. This will be achieved with the full cooperation and effort between partners to promote the company. Thus, this will be our motivation to make our products more profitable and stable for the long term.